Abiogenic gas seepage from serpentinite at Tanjung Api, Tomini Bay, East Sulawesi - van Gorsel, J.T.; Subroto, E.A. (Berita Sedimentologi, 2022)
Oil and gas seeps are common across the Indonesia region and are usually associated with breached anticlines or faults in Cenozoic or Mesozoic sedimentary basins, where they were generated from biogenic or thermogenic conversion of organic matter in sediments. In contrast, the methane gas at Tanjung Api in East Sulawesi is emerging from an area of ultramafic mantle rocks, which are part of the large East Sulawesi Ophiolite Complex.Tanjung Api is a prominent cape along the South side of Tomini Bay (also called the Gorontalo Basin, along the north shore of the East Arm of Sulawesi). The name means ‘Fire Cape’ and reflects the presence of several burning gas seeps on the beach. This phenomenon must have been active and known for more than 150 years, as the name was already shown on Dutch topographic maps in 1869, and possibly earlier.In this brief review of the enigmatic Tanjung Api gas seeps, we argue that the gas is not a conventional, organic-derived hydrocarbon gas, but an abiogenic (or abiotic), gas, dominated by isotopically anomalous methane and hydrogen, which formed from the serpentinization of ultramafic rocks.